INVESTOR’S MINDSET TOWARDS IPO AS AN INVESTMENT TOOL USING NON PARAMETRIC TESTS - Sahu, Puja Archana; Sajjan, Rohini (International Journal of Psychosocial Rehabilitation, 2020)
In India IPOs are most predominantly & popularly used method to raise fund from general public. But many studies have failed to know their reasons of popularity.. Hence, this study aims to understand the reasons for the popularity of IPO as an investment tool & explore various avenues of information about IPO. Authors used Mann Whitney U test & Kruskal Wallis methods to test hypothesis by using SPSS. It is found that majority of the dependent variables are different across the genders and shown an attitudinal difference across qualification and income categories.